Technical and inspirational philosophy of law: Lawyers' reasoning and artificial intelligence - Spaić Bojan (Glasnik Advokatske komore Vojvodine, 2025)
The paper examines the relationship between the philosophy of law and legal practice. It is argued that the philosophy of law is a reflection on law, which may take the form of inspirational or technical reflection. Both forms of the philosophy of law can engage with legal practice, but only technical philosophy of law is capable of addressing concrete legal problems. The approach of technical philosophy of law is illustrated in the paper through the consideration of legal reasoning and artificial intelligence. The paper concludes by reflecting on the importance of the philosophy of law for legal practice.